Planting Mathematics Concepts for Low Grade Elementary Schools through the Traditional Games - Nuraeni, Zuli; Rusnilawati (EDUPEDIA Publisher, 2022)
A common problem in mathematics education in Indonesia is the low interest in mathematics because students learning mathematics is learning to memorize formulas which they then formulate to solve problems. For elementary school students, this learning will be very boring and do not interact at all because they are far from those who still like to play. This paper will discuss the planting of math concepts for low-grade elementary schools through traditional games, according to local wisdom-based mathematics learning so that mathematics lessons are no longer a scourge for elementary students but become fun mathematics because children can learn mathematics from their games. Many studies have found that game strategies are effective in motivating children to learn mathematics and at the same time making the learning stop. The focus of this paper is on examples of traditional games that can support the learning process of mathematics and the role of the teacher in facilitating mathematics learning that isn’t directly integrated into the game.